An empirical investigation of agility factors in select Indian manufacturing industries. (2018) - Khatri, Alok; Garg, D.; Dangayach, G.S.
In the era of dynamic and customised demand, the organisations cannot be rigid. Rigidity can be reduced by adopting agile manufacturing paradigm. The objective of this study was to identify chief predictors of agile manufacturing and to distinguish agile developers and enablers. The survey-based study has been conducted to identify and pinpoint factors of agility to help managers to identify the areas to be focused. A hypothetical agile manufacturing framework has been proposed. The study indicates that nine hypothesised factors have statistically significant relationship with agility. Linear regression model has been developed to recognise agile manufacturing predictors. Linear regression model equation of agile manufacturing has been compared and tested with the mean value of agility. The results obtained from linear regression model and survey was found to be in close proximity. Further using principal component analysis, proposed empirical framework has been restructured as per empirical results of study.